An electro-hydrostatic actuator for hybrid active-passive vibration isolation. Issue 1 (2018) - Henderson, Jean-Paul; Plummer, Andrew; Johnston, Nigel
A novel electro-hydrostatic actuator (EHA) for active vibration isolation has been designed, modelled and tested. The EHA consists of a brushless DC motor running in oil and integrated with a bidirectional gear pump, driving a hydraulic cylinder. The actuator is designed to be integrated into a flexible strut connecting a helicopter rotor hub and fuselage, to provide isolation at the dominant rotor vibration frequency of around 20 Hz. The resonant frequency of the EHA is tuned to provide some passive vibration isolation. Active control increases the isolation performance by compensating for damping losses, and provides isolation over a broader range of frequencies. Tests on a prototype demonstrated a four-fold reduction of the root-mean-square transmitted force and a near elimination at the fundamental frequency. The advantages of the resonant EHA are a wider range of operating frequencies than a purely passive system, and lower power consumption than a purely active system.